Desmitificar la violencia: crítica al discurso (técnico) de la seguridad ciudadana - Moriconi, M. (Revista Mexicana de Sociología, 2011)
Citizen security has become one of the main topics in Latin American political science. Despite the abundant literature on the subject, a genealogical tour of this discursive tradition reveals a number of cognitive limitations. There is a prevalence of technical thinking that creates a supposedly apolitical narrative when it comes to combating violence and eliminates the possibility of a political debate that does not focus only on the objective violent event but rather on understanding the scope of the good life. In this respect, this paper seeks to review the criteria of veracity of contemporary society as focuses of malaise.